2011
DOI: 10.1111/j.1745-4549.2011.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Edible Starch-Based Coating Including Glycerol Plus Oleum Nigella on Arils From Long-Stored Whole Pomegranate Fruits

Abstract: Two concentrations of cold‐pressed seed oil at a 300 and 600 ppm of Nigella sativa incorporated into starch‐based edible coating were applied onto pomegranate arils. Arils were individually treated with a solution of only starch coating (starch + glycerol, 2:1, v/v), 300 ppm oil + starch coating (starch + glycerol, 2:1, v/v and N. sativa oil, 300 ppm) and 600 ppm oil + starch coating (starch + glycerol, 2:1, v/v, N. sativa oil, 600 ppm). The untreated arils were used as the control group. All treatment groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 39 publications
(123 reference statements)
9
50
0
1
Order By: Relevance
“…Pomegranate arils coated with chitosan and ascorbic acid showed no signs of deterioration, which rendered them acceptable for consumption. The findings obtained also showed that the a* value, which is related to the color stability and redness was significantly higher in the chitosan coated arils than in the control samples after 28 days of storage (Özdemir and Gökmen, 2017). It has been reported that the coating with chitosan and ascorbic acid significantly reduced bacteria, yeast and mold populations throughout the storage time (Ozdemir and Gökmen, 2017).…”
Section: Effect Of Coating Treatments On Pomegranate Aril Qualitysupporting
confidence: 54%
See 4 more Smart Citations
“…Pomegranate arils coated with chitosan and ascorbic acid showed no signs of deterioration, which rendered them acceptable for consumption. The findings obtained also showed that the a* value, which is related to the color stability and redness was significantly higher in the chitosan coated arils than in the control samples after 28 days of storage (Özdemir and Gökmen, 2017). It has been reported that the coating with chitosan and ascorbic acid significantly reduced bacteria, yeast and mold populations throughout the storage time (Ozdemir and Gökmen, 2017).…”
Section: Effect Of Coating Treatments On Pomegranate Aril Qualitysupporting
confidence: 54%
“…Oz and Ulukanli (2012) reported that there were statistically significant differences between the control and coating treatments throughout the storage. At the end of the storage, a 6% weight loss was measured in the control group, 3% in the starch coating itself, 2% in 300 ppm and 1% in 600 ppm oil + starch coating-treated arils (Oz and Ulukanli, 2011).…”
Section: Effect Of Coating Treatments On Pomegranate Aril Qualitymentioning
confidence: 99%
See 3 more Smart Citations